Relationship between salivary mucin or amylase and the periodontal status. (22nd November 2012) - Sánchez, GA; Miozza, VA; Delgado, A; Busch, L
<x xml:space="preserve">Abstract</x> Objective Here we determine the relationship between salivary levels of mucin and amylase and the clinical parameters of periodontal disease before and after periodontal treatment. Subjects Ninety two subjects were clinically examined and distributed into four groups namely clinically healthy, mild, moderate and severe periodontitis, according to the periodontal status, classified according the values of clinical attachment level (CAL) and probing pocket depth (PPD). Unstimulated saliva was collected for 5 min. Salivary proteins, amylase and mucin were determined by colorimetric methods. Results A significant positive correlation (P < 0.0001) was observed between salivary mucin, amylase or protein and PPD or CAL before periodontal treatment while flow rate showed a negative correlation. Mucin and amylase output also showed a positive correlation with PPD or CAL. After treatment, the improvement of clinical parameters was accompanied by a diminution of salivary mucin, amylase or protein concentration and output in moderate and severe group. Conclusions The increment of mucin and amylase output in relation to periodontal status indicates that salivary glands respond to the disease by increasing the protective potential of saliva when necessary and return to the normal rate of secretion after the resolution of the inflammatory process.